Impact of Access to Subsidized Certified Improved Rice Seed on Income: Evidence from Rice Farming Households in Nigeria - Awotide, B.A.; Awoyemi, T.T.; Diagne, A. (2012)
Seed certification enhances seed quality and has the potential to increase rice yield and improve farmers’ income. Rice farmers in Nigeria were granted access to certified improved rice seed at a subsidized rate using the seed voucher system by the Emergency Rice Initiative (2008-2010), formulated by AfricaRice, in response to the global food crisis of 2008, in order to mitigate the adverse effects on poor farmers. The impact of access to the Subsidized Certified Improved Rice seed (SCIRS) on farming households’ income has not been documented. Hence, this study was conducted to fill this gap. The data were collected using a multistage random sampling technique. Osun, Niger and Kano states were selected to represent - upland, lowland and irrigated rice growing systems, respectively. Five major rice-producing Local Government Areas (LGAs) were selected from each state, followed by the selection of three villages from each LGA. In all, 600 rice farmers were selected on the basis of probability proportionate to the population size of rice farmers in the villages, out of which 160 farmers were randomly selected to receive the SCIRS (treatment group) and the rest were not given (control group). Data were collected using a structured questionnaire and analyzed using descriptive statistics, ATE estimation method and the Local Average Treatment Effect (LATE) estimation techniques. The result revealed that average income from rice production and per capita household income increased by 18.5% and 2.3% respectively at the end of the intervention in 2010. The result of the LATE showed that access to SCIRS increased income from rice production by N50, 220.55 per cropping season, thereby reducing the farmers’ probability of being poor. Therefore, timely access to seed of good quality can be a route out of the present prevailing rural poverty in Nigeria. It is recommended that seed certification should be intensified.